THU0339 Power doppler ultrasonograpic findings in healthy pediatric enthesises. (23rd January 2014) - Ravagnani, V.; Pieropan, S.; Barausse, G.; Sidoti, G.; Boner, A.; Volpe, A.; Caramaschi, P.; Biasi, D.; Adami, S.
Abstract : Background: In Rheumatic Ultrasonographic evaluation interest has been raised about the use of power Doppler ultrasonography (PDUS) in the assessment of inflammatory changes in the articular and periarticular structures of children.Nevertheless, there are methodological and interpretative problems due to a lack of ultrasound definition of both the normal joint components and their physiological vascularization in the young population. Objectives: To perform PDUS examination of the principal enthesises of healthy children, focusing particularly on their vascularization. Methods: We enrolled 33 children (age between 2 and 12 years) Children were assessed by an expert pediatric rheumatologist in order to exclude subjects with clinical history or evidence of muscoloskeletal diseases. The same day a rheumatologist, performed a PDUS examination of the enthesises. The following enthesises were scanned: distal quadriceps tendon, distal and proximal patellar ligament, distal Achilles tendon, medial and lateral epicondyle tendons of the elbow. According to the OMERACT the following elements were evaluated: enthesis thickness, structure or calcifications, bone proliferation, erosions.Vascularization at enthesis level was judged as present or absent in three areas: 1) at the outer edge of the enthesis (peripheral vessel), 2) inside the enthesis (intratendinous vessel), 3) inside the epiphyseal cartilage at the insertion of the enthesis (cartilaginous vessel). Results: The remaining 31 subjects were 18 girls and 13 boys, average age 8 years (±2.9). 256 enthesises were evaluated: 180 enthesises of the knee, 40 Achilles enthesises, 36 elbow enthesises. In the gray scale no abnormalities in the enthesises, in the cortical bone or epiphyseal cartilage were idientified. 1) The power Doppler examination showed at least a peripheral vessel around the quadriceps enthesis in 43% of the subjects, around the proximal patellar enthesis in 20%, around the distal patellar enthesis in the 10%, around the Achilles enthesis in the 5%, none around the lateral epicondyle enthesis and in the 22% of subjects around the medial epicondyle enthesis of the elbow. The quadriceps and superior patellar peripheral vessels usually go into the middle part of the patella.2) An intratendinous power Doppler signal was found only in the quadriceps enthesises and it was detected in the 23% of the subjects; this vascular signal appeared always in the same area, that was the distal part of the enthesis, near to the superior pole of the patellar cartilage.3) Cartilagineous vessels adjacent to the enthesis were found close to the quadriceps tendon in the 20% of subjects, close to the proximal patellar tendon in the 30% of the cases, close to the distal patellar tendon in the 47% of the children, close to the Achilles tendon in the 10% of the entheses, close to the lateral epicondyle entheses of the elbow in 67% of the subjects and in the 47% of subjects close to the medial epicondyle entheses of the elbow. Conclusions: Power Doppler examination of pediatric enthesis in healthy children can show physiological vessels. These vessels are mainly peritendineus or cartilaginous.Intratendineous vascularization is absent in healthy enthesis, except for the distal part of quadriceps tendon and this finding could represent a pitfall if detected within a context of disease Disclosure of Interest: None Declared